New assignment of the adenosine deaminase gene locus to chromosome 20q13 X 11 by study of a patient with interstitial deletion 20q. Issue 2 (February 1987) - Petersen, M B; Tranebjaerg, L; Tommerup, N; Nygaard, P; Edwards, H
Abstract : A karyotype 46, XY, del(20)(q11 X 23q13 X 11) was found in a three year old boy with mental and growth retardation, low set ears, broad nasal bridge, and macrostomia. Adenosine deaminase (ADA) activity was reduced by about 50%, assigning the gene locus to the deleted segment. A review of the previously reported regional assignments suggests that the ADA gene is in the region of band 20q13 X 11.